The End of the Rights of Man in Sweetness in the Belly - Dhungana, Anima (Literary Studies, 2023)
Gibb’s Sweetness in the Belly is as an example of brutal and inhumane behaviour of the state apparatus during the political turmoil in the world after Second World War, especially in Africa. The novel presents the pathetic condition of the inhabitants of the colonized nations and the trauma experienced by people from different roots through the presentation of the major character Lily, who ends up in refugee status. Furthermore, Amina and her husband Yusuf, lives their lives with the psychological and physical imparity even long after their heart rendering dehumanized experience. Aziz, the doctor, despite his pleasant character faces premature death as a consequence of brutal act on its citizens by the nation-state. I, therefore, argue that the novel presents a perfect example of ruthless treatment of imperialism, totalitarian rule, and domination by the exercise of repressive state apparatus resulting in the deprivation of the Rights of Man caused by the Decline of the nation states, to compel major character Lily into refugee status, Amina and her husband, Yusuf into psychological and physical imparity, and Dr. Aziz’s unnatural tragic death. Before bringing up the arguments to support my claim, it is important to understand the varied meaning of Human Rights and historical timeline of the novel.